Effectiveness of Acceptance and Commitment Therapy on Emotional Self-Regulation and Sense of Coherence in Patients with Irritable Bowel Syndrome - Balali, Donya; Salehi, Leila; Changi Ashtiani, Mojtaba; Solat, Farya; Menat Ali, Shahram; Alavi, Seyyed Hossein (Health Nexus, 2023)
Emotions and psychological states significantly affect the severity of symptoms in Irritable Bowel Syndrome (IBS), with patients experiencing considerable distress due to various physical symptoms and negative emotions. The present study aimed to examine the effectiveness of Acceptance and Commitment Therapy (ACT) on emotional self-regulation and sense of coherence in patients with IBS. This study employed a quasi-experimental pre-test, post-test design with a control group and a two-month follow-up period. The population consisted of patients with IBS who visited the Gastrointestinal and Liver Research Center in Tehran in the first quarter of 2023. Thirty patients were selected through purposive sampling and randomly assigned to experimental and control groups. The experimental group received ACT in ten 90-minute sessions, once a week. The instruments used included the Gross and John (2003) Emotional Self-Regulation Questionnaire and the Felsenberg et al. (2006) Sense of Coherence Questionnaire. Data were analyzed using repeated measures analysis of variance with SPSS version 26. The results showed that ACT significantly impacted emotional self-regulation (p=0.002, F=11.57) and sense of coherence (p=0.004, F=9.88) in patients with IBS. It can be concluded that ACT can be an effective intervention for improving emotional self-regulation and sense of coherence in patients with IBS.